MOTIVASI BELAJAR MATAKULIAH PENCAK SILAT PADA MAHASISWA PESERTA UNIT KEGIATAN MAHASISWA PENCAK SILAT (Studi pada Mahasiswa Jurusan Pendidikan Olahraga Angkatan 2014) - hamdani hamdani (Journal of Sport Science and Education, 2017)
Abstract, Motivation takes an important role to achieve success in learning, especially for pencak silat learning in physical education department. This research used descriptive method for physical education department student in grade 2014. The aim of this research is to know about intrinsic motivation and extrinsic motivation to learn pencak silat subject of student who participate in pencak silat Student Activity Unit.This research used questionnaire as the research instrument. The population of this research is the students of physical education department in grade 2014 who have never get pencak silat subject and now they have become the participant of Pencak Silat Student Activity Unit that have 146 participants.The result of this research use percentage that divided in three categories, high, fair, low. The students who have high category in intrinsic motivation is 53.42% and have frequency 78, in fair category get  13.70% percentage and 20 frequency. Then in extrinsic motivation, the student who have high category, get percentage 25.34% and have frequency 37, the fair category have 7.53% percentage and 11 frequency.The conclusion of the research, showing that the motivation in learning pencak silat subject of students who join pencak silat Student Activity Unit have more dominant in intrinsic motivation with 53.42% percentage (high category). keyword : learning motivation, pencak silat